Morphological changes of annular ligament at stenosing ligamentitis of the fingers of the hand. - Kvasha, V. P.; Kovalchuk, D. U.; Dralov, Ya. S.; Bondarenko, N. N.; Brusco, A. T. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. According to the data of the world literature among the diseases of the tendon-ligament apparatus of the hand, the processes of stenosis of the fibrous channels amount to 43.8%, and the stenosing ligamentitis of the fingers of the hand - up to 22.3% of cases. The pathogenesis of the disease is not fully established. Objective. To complete knowledge of the pathogenesis of stenosingligamentitis of the fingers of the hand through histological and morphometric studies. The study material was biopsy specimens of the altered ring-shaped ligament in 57 adult patients received during surgery. For a comparative assessment of morphological changes, 11 ring-shaped ligaments in corpses without a common pathology and local manifestations of the hand were examined. Results. In untreated patients (group I), with an increase in the duration of the disease, signs of lymphocyte-cell infiltration, edema of the ring-shaped ligament and distrofic-degenerative changes accompanied by a decrease in the fibrillar component and the appearance of chondrogenic foci increased. In patients of the second group, the pathological process was characterized by the lymphocyte-fibroblastic phase of independence from the duration of the disease. At the same time, changes in the cellular composition of fibrous connective tissue prevailed. Conclusion. In patients of group I, an increase in the specific area of the main amorphous substance was determined 7.92 times and 2.57 times the macrophage-lymphocytic infiltrates of endothendinia and perithendinium, and in endothendia they were accompanied by collagenolysis and foci of ectopic chondrogenesis. In patients of group II, the proportion of the area of endothendia increased by 42.46% due to early violations of the architecture of the ligament fibers and lymphocytic infiltration; in the epithendia, the hypercellular regions were determined with dense hyperchromicfibrocytes. After 12 months The specific area of the endothendia increased by 4.76 times.